2020
DOI: 10.12963/csd.20745
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Korean-Version of the Youth Attitudes toward Noise Scale

Abstract: The purpose of this study was to develop a Korean-version of the Youth Attitudes to Noise Scale (K-YANS) reflecting the primary causes of noise-induced hearing loss (NIHL): exposure to loud sounds in noisy places and unsafe listening practices on personal listening devices (PLDs). Methods: We translated the English-version of the YANS, which included 19 question items with four factors and selected four additional items relevant to youth's listening practices on PLDs. A total of 321 Korean college students com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The third section of the survey asked the participants a question about the use of hearing protection. The last section focused on the K-YANS (Han & Kim, 2020).…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The third section of the survey asked the participants a question about the use of hearing protection. The last section focused on the K-YANS (Han & Kim, 2020).…”
Section: Surveymentioning
confidence: 99%
“…Results demonstrated that the association between having experience with at least one hearing symptom and a negative attitude toward noise would lead to hearing protection use because the noise produced in those activities is widely considered harmful and the use of hearing protection is taken into consideration. These findings suggest the importance of socio-cultural contexts in evaluating college students' attitudes toward noise (Han & Kim, 2020;Widén et al, 2009) because these contexts can influence their use of hearing protection and even hearing status. For example, Keppler et al (2015) study with young adults in Belgium found that college students with a negative attitude toward noise had significantly less hearing loss and used hearing protection devices more frequently than those who had positive attitudes, indicating that college students who don't perceive noise as problematic tend to use hearing protection with less frequency and already have a more deteriorated hearing status.…”
mentioning
confidence: 99%